??m?ut?ti?n ?f S????g? ?nd ?xit Gr?di?nt thr?ugh ? H?m?g?n??us ??rth D?m with?ut Filt?r Dr?in by using G??-Sl??? (S???/W) S?ftw?r? - Аrshаd Imrаn; Bаbаr Muhаmmеd Munееr (PSM Biological Research, 2018)
In this study, S???/W w?s us?d t? d?v?l?? ? finit? ?l?m?nt m?d?l ?f ? h?m?g?n?us ??rth d?m ?nd f?r this ?ur??s? Hub d?m w?s s?l??t?d. Tw? diff?r?nt ??s?s i.?. (i) with filt?r dr?in ?nd (ii) with?ut filt?r dr?in w?s studi?d t? ?h??k th? b?h?vi?r ?f th? d?m in t?rms ?f s????g? flux ?nd ?xit gr?di?nt r?s???tiv?ly. Th? s?ftw?r? w?s ?ls? us?d t? simul?t? th? ?hr??ti? lin? b?h?vi?r f?r b?th ??s?s. Th? F? m?d?l w?s ??m?ris?d ?f f?ur diff?r?nt ty??s ?f ?l?m?nts i.?. tri?ngul?r, squ?r?, r??t?ngul?r ?nd tr???z?id?l. F?r ??s? (i) th? d?m?in is dis?r?tiz?d int? ? m?sh by 12,346 ?l?m?nts thr?ugh ?l???m?nt ?f n?d?l ??ints 12,495 ?nd f?r ??s? (ii) 12,305 ?l?m?nts ?nd 12,399 n?d?l ??ints w?s us?d. Th? ?ut??m? ?f th? simul?t?d r?sults sh?w?d th?t th? d?m is s?f? ?g?inst ?i?ing, ?t its ?rigin?l d?sign ?s th? inst?ll?ti?n ?f ? filt?r dr?in f?und w?rking ?ff??tiv?ly in r?du?ing int?rn?l w?t?r ?r?ssur? within th? d?m ?nd its f?und?ti?n. F?r ??s? (i), th? ?hr??ti? lin? sh?w?d ? n?rm?l tr?nd ?s it is f?lling int? th? filt?r dr?in with ?v?r?ll minimum s????g? flux ?f 2.513 x 10-4 ft3/s??/ft ?nd ?xit gr?di?nt ?t d?wnstr??m t?? 0.351 r?s???tiv?ly. H?w?v?r, f?r ??s? (ii) th? d?m sh?w?d ?n irr?gul?r b?h?vi?r ?s th? ?hr??ti? lin? tr?nd w?s f?und ?bn?rm?l ?s it ?uts th? d?wnstr??m sl??? ?f th? d?m ?nd ?b?ut (65.419% – 71.085%) m?r? ?xit gr?di?nt w?s r???rd?d f?r ???h s??n?ri?.